Babylon 5's blueprint for the archetypal heroes of Commander Jeffrey Sinclair and Captain John Sheridan with Ambassador Delenn. - Iaccino, James F. (Journal of Popular Culture)
The writer discusses the portrayal of heros in Joe Straczynski's science-fiction television program Babylon 5 during its unprecedented five-season run during the 1990s. He outlines some of the salient characteristics of the archetypal hero before focusing on two of the more central figures of the Babylon 5 series, namely, Commander Jeffrey Sinclair and Captain John Sheridan. He asserts that the show is prototypic in its portrayal of the archetypal dimensions of the hero and contends that the Straczynski story arc has contributed to each of the heros' growth and development and served as the model for more recent science-fiction series.